Love Thy Body: Answering Hard Questions about Life and Sexuality - Pearcey, Nancy R. (Baker Books, 2018)
Bestselling author and cultural commentator helps readers cut through the culture-war rhetoric and equips them to respond intelligently and compassionately to issues such as abortion, assisted suicide, homosexuality, transgenderism, and more